Optimizing Financial Governance in Improving the Performance of the Plelu Meluk Wolokoli Kopdit Savings and Loan Cooperative - Woi, Patrisius; Sanga, Konstantinus Patti; Aurelia, Pipiet Niken (Neo Journal of economy and social humanities, 2024)
This study aims to find out the optimization of financial governance in improving the performance of credit cooperatives in KSP Plelu Meluk Wolokoli. This research focuses on how the internal and external factors of savings and loan cooperatives are managed in cooperative institutions that are closely related to cooperative members. This study uses a qualitative descriptive method. An interview was conducted with the management of KSP Kopdit Plelu Meluk Wolokoli. The results of the study show that KSP Kopdit Plelu Meluk Wolokoli is considered not optimal in realizing the annual budget planned through mutual agreement. KSP Kopdit Plelu Meluk Wolokoli is considered not optimal in financial audit because the implementation of financial audit (KSP Supervisor Kopdit Plelu Meluk Wolokli) the audit is not as routine and not by the rules set. KSP Kopdit Plelu Meluk is also considered not optimal in managing assets and residual business results (SHU).